Good debt, bad debt, and MSME performance in Indonesia - Khaer, Fawaz Muhammad (Central Community Development Journal, 2024)
Micro, small, and medium enterprises (MSMEs) dominate Indonesia’s economy yet remain constrained by costly, mismatched, and shock-fragile borrowing. This study reframes “access to credit” into “quality of debt” and quantifies how design and use of loans translate into firm outcomes. Using a mixed-methods approach that links transaction-level sales (QRIS, marketplace backends), lender product files, and a structured owner survey, we construct a Debt Quality Index (DQI) capturing three pillars: payback coverage, maturity–asset-life fit, and downside resilience. We analyze 2,146 MSMEs across provinces and sectors with firm-month panels and event-study designs around product rollouts (e.g., revenue-linked installments, short payment holidays, movable-asset lending). Results are blunt: higher DQI is consistently associated with faster revenue growth, lower delinquency, and smoother cash paths. A one-standard-deviation lift in DQI aligns with 2.1–2.6 percentage-point gains in monthly revenue growth and 1.8–2.2 percentage-point reductions in 30–90 day delinquency, after rich controls. Mechanisms run through better cash-flow matching and resilience to negative demand shocks. Effects are stronger for owners with higher debt literacy and for firms with dense digital transaction trails that enable precise tenor calibration. Policy and practice are clear: subsidizing “more loans” is not enough—programs should target productive leverage by conditioning support on DQI thresholds, mandating total-cost and maturity-fit disclosures, and scaling movable-asset and revenue-linked structures. The contribution is a field-ready metric and evidence base that lets owners, lenders, and policymakers separate good debt that pays back from bad debt that extracts value, at scale.